HLJ-Knipselkrant. - Homo- en Lesbiennejongerenkoepel (HLJK) (Izegem : HLJK, 1994)
Fonds Suzan Daniel (FSD)
Periodiciteit : driemaandelijks
Redactie : Krekelstraat 153, 8870 Izegem
Voortzetting van HLJK-Info
Nederlands
Periodiek